Preparing Agile Transformation: A Framework for Assessment of the Organizational Culture Readiness (Journal of Applied Business and Economics, 2021)
With disruptions reshaping the global economy, companies need to find a way to embrace constant change. Recently, “becoming Agile” has been the motto of organizational change. However, more than half of all organizations have at least one agile transformation project fail, often due to an unsuitable organizational culture. This research provides a framework to assesses organizational culture’s readiness for Agile, by integrating existing models in the areas of change management, organizational, and Agile culture which may help companies to identify possible deficiencies in the organizational culture that can then be targeted prior to the Agile transformation.
Keywords: business; economics; organizational culture; Agile organization; readiness assessment